Navigating Hybrid Pedagogies in English for Business: Insights from Indonesian Higher Education - Hamid, Restu Januarty; Noni, Nurdin; Sunra, La; Sakkir, Geminastiti (Pascasarjana Universitas Negeri Makassar, 2025)
This study explores the challenges and adaptive strategies employed by lecturers in implementing hybrid learning for English for Business (EfB) instruction within an Indonesian higher education context. Grounded in Connectivism, Sociocultural Theory, and Bloom’s revised taxonomy, the study employs a qualitative descriptive design involving semi-structured interviews with four experienced EfB lecturers, classroom observations, and document analysis. Thematic analysis revealed four interrelated domains: (1) disparities in access to technology and digital fluency, (2) limited interactional engagement in online settings, (3) underdeveloped information-management skills among students, and (4) lecturer readiness and workload concerns in hybrid environments. Findings indicate that infrastructural limitations and the digital divide significantly constrain equitable participation and pragmatic language use in hybrid classrooms. However, proactive instructional strategies such as the provision of offline materials, structured micro-tasks, and embedded digital literacy training can mitigate these challenges. The study underscores the centrality of technological, pedagogical, and institutional connectivity in shaping hybrid learning outcomes. It contributes to the growing body of HyFlex and ESP scholarship by offering context-rich insights from the Global South and provides implications for educators, institutional leaders, and policymakers seeking to design inclusive and resilient hybrid learning systems.